Self-evaluation guideline of overlapping spectrum sharing for multi-user MIMO cognitive radio systems - Rattasat Laikanok; Peerapong Uthansaku; Monthippa Uthansakul (Engineering and Applied Science Research, 2019)
This paper introduces a performance analysis of a multi-user spectrum sharing based the effect of node positions in an MIMO cognitive radio (CR) network. The objective is to develop and enable reliableCR technology. This paper: 1) develops the performance analysis to support multi-user CR systems, 2) describes the significant effect of each node position and the distance between them, 3) combines decision results on both downlink and uplink operations,and, 4) presents a spectrum allocation method for all users in CR systems. The simulation results show the performance of secondary users in terms of thebit error rate inside their coverage areas together with the effect of GPS error. Finally, a completeself-evaluation guideline of the overlapping spectrum sharing for multi-user CR systems is presented. The outcome of this paper is very useful to enhance CR systems. Also, it can be easily implemented in practice for spectrum sharing. The users can realize by themselves whether their positions are in the available area or not.